ANALISIS PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA BAGI HASIL (DBH) DAN BELANJA MODAL TERHADAP PERTUMBUHAN EKONOMI SERTA DAMPAKNYA PADA TINGKAT KEMISKINAN DI DAERAH KABUPATEN/KOTA PROVINSI RIAU TAHUN 2011-2015 - Putrayuda, T. Fahrurriza; Efni, Yulia; Kamaliah, Kamaliah (Jurnal Tepak Manajemen Bisnis, 2017)
This study aims to determine the effect of Earning Influence Income (PAD),(PAD), General Allocation Fund (DAU), Profit Share Fund (DBH), CapitalExpenditure, and Economic Growth on Poverty Rate through Economic Growth atRegency / City in Riau Province 2011-2015 . The study was conducted for 2 months,from October to December 2016.The object of this study is the district / city in Riau Province, the population and sampleused in this study are 12 districts / municipalities in Riau Province. The data used aresecondary data obtained based on documentation of the results of BPS publication(Central Bureau of Statistics) for data on Economic Growth and Poverty Rate whereasdata of Earning Influence Income (PAD), General Allocation Fund (DAU), DBH andCapital Expenditure Obtained from the Financial Management Agency and RegionalAsset (BPKAD) Riau Province. The analysis tool used is Path Analysis using PartialLeast Square (PLS) method.The result of the research indicates that Pendapatan Asli Daerah (PAD), Profit SharingFund (DBH), Capital Expenditure, and Economic Growth have a significant effect onPoverty Level directly. While the General Allocation Fund (DAU) has no significanteffect on Poverty Rate directly. Indirectly through the Economic Growth of LocalOriginal Income (PAD), Profit Sharing Fund (DBH) and Capital Expenditure have asignificant effect on Poverty Level. While the General Allocation Fund (DAU) indirectlyor through Economic Growth does not affect the Poverty Level. Economic Growth as anintervening variable plays an important role in increasing the influence of LocalRevenue (PAD) and Capital Expenditure on Poverty Level, but has no role inincreasing the influence on General Allocation Fund (DAU) and influence DBH.